A Comparative Analysis of Occupational Health and Safety Practice Implementation in Public and Private Construction Sectors: A Policy Harmonization Case Study - Hayder, Farah; Jaf, Dilshad; Oztas, Ahmet (Engineering, Technology & Applied Science Research, 2026)
The construction sector is a high-risk industry for Occupational Health and Safety (OHS). The rapid pace of construction has raised questions about the efficacy of OHS at public- and private-sector project sites. This study compares OHS practices, hazard types, and accidents across construction sites operated by public- and private-sector organizations. Data were collected through a comparative, cross-sectional survey of 422 construction workers, supervisors, and managers working at public- and private-sector construction sites in the Kurdistan Region of Iraq, using a structured questionnaire. The questionnaire covered key OHS domains, including safety training, use of Personal Protective Equipment (PPE), accident-reporting processes, and general safety culture. The data were then examined using descriptive statistics and comparison tests (chi-square tests and t-tests) to report differences across sectors. The results indicate that compliance with OHS practices, including safety training, the availability of PPE, and the implementation of formal accident-reporting systems, was higher at public-sector construction sites. Private sector facilities, despite having some strengths, were found to have more variability and lower overall adherence to OHS practices. There are significant disparities (p < 0.05) in OHS between public and private sector construction sites in the Kurdistan Region of Iraq. To address these disparities and enhance Health and Safety (HS) outcomes for construction workers, the study proposes increased regulation and targeted policy interventions, particularly for the private sector.